AKTIVITAS BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA PADA MASA PANDEMI COVID-19 - Suci Aprilia; Zubaidah R; Dona Fitriawan (Jurnal AlphaEuclidEdu, 2022)
This study aims to find out how students' learning activities in learning mathematics during the covid-19 pandemic at SMK Negeri 03 Pontianak. The research method used is descriptive with the type of qualitative research. The research subjects were 37 students of class XI Accounting 2 who took part in mathematics lessons during the covid-19 pandemic. The results of data analysis showed that student learning activities in learning mathematics during the pandemic at SMK Negeri 03 Pontianak were in the "quite active" category. With three indicators which include student’s writing activities in learning mathematics during covid-19 pandemic at SMK Negeri 03 Pontianak were in the “quite active” category, student’ drawing activities in learning mathematics during the covid-19 pandemic at SMK Negeri 03 Pontianak were in the “quite active” category, and students’  motor activities in learning mathematics during the covid-19 pandemic at SMK Negeri 03 Pontianak were in the “quite active” category.